2010
DOI: 10.1099/jmm.0.016964-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and molecular characterization of extended-spectrum β-lactamase-producing Proteus mirabilis strains in southern Croatia

Abstract: The aim of this study was to determine the prevalence and antibiotic resistance rates of extendedspectrum b-lactamase (ESBL)-producing Proteus mirabilis strains isolated from inpatients at the Split University Hospital (southern Croatia) during a survey performed between 2005 and 2008. A total of 2152 consecutive isolates of P. mirabilis were isolated. The prevalence was 0.5 % in 2005 and increased significantly to 20.9 % by 2008. Strains were most frequently isolated from urine (36.5 %) and bronchial aspirate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The outcomes of this study would be helpful in designing further extensive investigations covering more poultry farms from expanded areas of the country to find nationwide prevalence of this zoonotic human pathogen. Emerging of MDR poultry-origin P. mirabilis has increased over the recent years [8,10,16,26], remains comparable to that of ours. In this study, isolates from chicken droppings showed high resistance properties towards tetracycline, nalidixic acid, ampicillin trimethoprim-sulfamethaxole and gentamycin.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The outcomes of this study would be helpful in designing further extensive investigations covering more poultry farms from expanded areas of the country to find nationwide prevalence of this zoonotic human pathogen. Emerging of MDR poultry-origin P. mirabilis has increased over the recent years [8,10,16,26], remains comparable to that of ours. In this study, isolates from chicken droppings showed high resistance properties towards tetracycline, nalidixic acid, ampicillin trimethoprim-sulfamethaxole and gentamycin.…”
Section: Discussionsupporting
confidence: 75%
“…Such malpractices in antimicrobial uses have been reported to exert selection pressure of antimicrobial resistance to gutmicrobial flora in poultry [13,14]; including recent evidences of multi drug resistance (MDR) P. mirabilis [9]. This P. mirabilis is known human pathogen as a common cause of human urinary tract infection (UTI), nosocomial infection, wound infection [15] and showed clear history of zoonosis in wide host ranges with emergence of MDR in recent years [10,16]. MDR P. mirabilis may therefore be transmitted among PFworkers who in turn may transmit that in surrounding environment thus infecting the catchment population at large.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36, 3840] Previous studies from 2005 to 2011 in Korea reported incidences of ESBL-producing P. mirabilis of 6.5–12.6%, but no information regarding the change in incidence over time was provided. [16, 18, 43] In this study, the prevalence of ESBL production among P. mirabilis bacteremia isolates was 22.6% over an 8-year period, which is higher than that reported by previous studies in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Serratia liquefaciens had been implicated in the contamination of chicken carcasses (Lahellec et al, 1975) and it is also occasionally isolated from clinical specimens, although its pathogenic role has not been established (Grimont and Grimont, 1984). The presence of Proteus mirabilis in poultry meat had also been documented (Kim et al, 2005, Wong et al, 2013, and the presence of Proteus species in chicken droppings had been acknowledged as one of the route of its transmission as a zoonotic pathogens to vulnerable workers while handing infected chicken directly (Tonkic et al, 2010) or through fecal-contaminated poultry products as other Enteric bacteria (Lima-Filho et al, 2013). A more current report also associated poultry-borne Proteus species with zoonotic urinary tract infection (Armbruster et al, 2014).It was also associated with rheumatoid arthritis that is common in developing countries (Ebringer and Rashid, 2014).…”
Section: Discussionmentioning
confidence: 99%